Multidrug resistant tuberculosis risk factors in Makassar, Indonesia - Burhan, Siti Latifah; Wahiduddin, Wahiduddin; Maria, Ida Leida; Bustan, M Nadjib; Saleh, Lalu Muhammad; Balqis, Balqis (Intelektual Pustaka Media Utama, 2024)
Multidrug resistant tuberculosis (MDR-TB) is a significant public health concern in Indonesia, resulting in substantial morbidity and mortality rates. This study aimed to quantify the impact of risk factors of MDR-TB. A case-control study was conducted at Makassar Community Lung Health Center (BBKPM) in Makassar City. A total of 132 respondents, 66 cases, and 66 controls have participated in the study. Data was analyzed using the Stata version 14 tool, odds ratio (OR), and multiple logistic regression. Multiple logistic regression analysis identified significant risk factors for the occurrence of MDR-TB include previous TB treatment (OR=8.46, 95% CI: 3.278-21.858), positive acid-fast bacilli (AFB) sputum (OR=6.40, 95% CI: 2.525-16.260), and adverse drug event (OR=3.45, 95% CI: 1.008-11.867). The probability of developing MDR-TB is 95.9% if there is previous TB treatment with cases of relapse/loss to follow-up/failed treatment, positive AFB sputum, and adverse drug event. The most dominant risk factor for the occurrence of MDR-TB is a previous TB treatment. We suggest that an efficient directly observed treatment shortcourse (DOTS) strategy, particularly in the management of adverse drug event, overseeing and supporting patients who have recovered from MDR-TB, involves the collaboration of MDR-TB healthcare professionals and patient supporters in the Yamali TB community, moving synergistically as an effort to MDR-TB control and prevention.